Pastorale begeleiding aan die persoon met dissosiatiewe identiteitsversteuring - A. L. du Plessis (Acta Theologica)
A person with Dissociative Identity Disorder (DID) is someone who was exposed to intense trauma impacting that person’s life negatively at various levels. Although dissociative identity disorder is described as a mental disorder in the DSM-IV, there are still unresolved issues regarding the phenomenon. Assistance should take place with care and sensitivity in order to guide the person with dissociative identity disorder taking into consideration integral dimensions of personal humanity. It is submitted that guidance in this respect can therefore not be unilaterally psychological or pastoral by nature. Effective assistance to the person implies an approach where different disciplines are part of a multidisciplinary support team. The question this article explores is how pastoral counselling may contribute to this approach in guidance of the person with dissociative identity disorder. A case study is discussed in which the conclusion is made that pastoral care has an effective role in the healing process of the person with dissociative identity disorder.